CORPORATE GOVERNANCE AND FINANCIAL TRANSPARENCY: EVIDENCE FROM INDONESIAN MANUFACTURING COMPANIES - Winoto, Surya Adi; Bandi, Bandi (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2024)
Corporate scandals enhance shareholders' concerns regarding the company's financial transparency. This study aims to examine the relationship between corporate governance and financial transparency. Multiple regression model is used to test the hypothesis on a sample of manufacturing companies listed on the Indonesian Stock Exchange from 2018 to 2022. The study find that financial transparency increases when frequency of audit committee activity and percentage of institutional ownership increases. However, the study find that independent commissioner has no impact on financial transparency.